Improvement of Work with Personnel as a Factor of Increasing Business Efficiency - Moskalenko, Anatoly Alekseevich (International Review of Management and Marketing, 2016)
The article is devoted to issues on improving the system of managing personnel of the gas and oil company on the basis of the fuller use of scientific approaches and methods. In the article the basic emphasis is made on the need to implement principles of the system approach when improving work with the research most fully reveals the issues related to improving the corporate training subsystem that must be progressive and cover the practice of not only the best national gas and oil companies but also companies of the world level. Basic principles of forming approaches to corporate training are systemized. The system model offered anticipates focus on the program and target technologies for prospective strategic projects and advance trainings with the use of foresight technologies are stipulated. In order to study and implement international experience, the reasonability of implementing programs on cooperating with foreign core businesses on separate aspects of training is defined. Suggestions given in the article can help managers of various levels of managing the gas and oil company, and functional managers to take timely, stipulated and well-reasoned decisions in the area of managing personnel to achieve strategic goals of business. Keywords: system approach, gas and oil company, corporate training, “goals tree”, management decisions JEL Classifications: J23, J29, M11, M12